Research on the Incentive Mechanism of the Pension Service Supply Chain under Asymmetric Information. (4th August 2021) - Chen, Xiaohua
Abstract : The information asymmetry between the pension service integrator and the pension service providers will affect the efficiency of the whole supply chain, and information sharing can solve this problem to a certain extent. To achieve information sharing, mutual trust is the first condition and mutual trust is also one of the important means of endogenous incentives. In this paper, the trust incentive coefficient is embedded in the principal-agent model. Considering the service capability coefficient, the communication degree coefficient, and the information sharing degree coefficient of the pension service providers, the trust incentive model of the supply chain of the pension service is constructed, the model is solved, and the conclusion is drawn. Finally, the correctness of the conclusion is verified by the numerical simulation using SAS software. The final results show that, under the condition of information asymmetry, the trust incentive coefficient of the pension service integrator to the pension service providers is positively correlated with the effort coefficient, the service capability coefficient, the communication coefficient, and the information sharing degree coefficient of the pension service providers, while it is positively correlated with the effort cost coefficient, the output sharing coefficient, and the risk aversion coefficient of the pension service providers. The variance of number and external environmental variables is negatively correlated. This research has shown that the trust is a means of incentive for pension service providers to share information. This research has a certain practical significance for improving the service efficiency of the pension services supply chain and optimizing the level of pension services.